Microsurgical Clipping of Anterior Choroidal Artery Aneurysms: A Systematic Approach to Reducing Ischemic Complications in an Experience with 146 Patients. Issue 4 (27th March 2019) - Winkler, Ethan A; Lu, Alex; Burkhardt, Jan-Karl; Rutledge, W Caleb; Yue, John K; Birk, Harjus S; Alotaibi, Naif; Choudhri, Omar; Lawton, Michael T
Abstract: BACKGROUND: Aneurysms of the anterior choroidal artery (AChA) have been associated with high treatment-associated morbidity due to ischemic complications. OBJECTIVE: To report a large clinical experience of microsurgically treated AChA aneurysms and describe a systematic approach to reduce ischemic complications. METHODS: One hundred forty-six patients with AChA aneurysms were retrospectively reviewed from a prospectively maintained database. Clinical characteristics, surgical techniques, clinical outcomes, arterial infarction, and use of intraoperative adjuncts (ie, ultrasonography, indocyanine green videoangiography, and neuromonitoring) were analyzed. RESULTS: In total, one hundred forty-three aneurysms (97.9%) were clipped. Temporary clipping was utilized in 47 cases (32.2%) with mean occlusion time of 5.6 min. Arterial infarction occurred in 12 patients (8.2%). In clipped aneurysms, 90.5% were completely obliterated, 8.8% had minimal residual (<5% of original), and 0.7% were incompletely occluded (>5% of original). Mortality (2.7%) was limited to patients with high-grade subarachnoid hemorrhage. Indocyanine green videoangiography and neuromonitoring altered operative technique in ∼20% of cases. Multivariate logistic regression identified intraoperative rupture as the sole predictor for arterial infarction. CONCLUSION: Open microsurgical clipping remains a safe, effective treatment for AChA aneurysms. Microsurgical technique is paramount in preserving AChA patency and reducing ischemic complications. Despite increasing reliance on qualitative measures of AChA blood flow (videoangiography and ultrasonography) and neurophysiological monitoring, these technologies aid us infrequently. However, these adjuncts provide important safety checks for AChA patency. Temporary clipping must be used judiciously to lower the risk of intraoperative rupture while limiting possible ischemia in the AChA territory.